2011
DOI: 10.1155/2011/258051
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Shiitake Mushroom (Lentinus edodes) Prevents Fat Deposition and Lowers Triglyceride in Rats Fed a High-Fat Diet

Abstract: High-fat diet (HFD) induces obesity. This study examined the effects of Shiitake mushroom on the prevention of alterations of plasma lipid profiles, fat deposition, energy efficiency, and body fat index induced by HFD. Rats were given a low, medium, and high (7, 20, 60 g/kg = LD-M, MD-M, HD-M) Shiitake mushroom powder in their high-fat (50% in kcal) diets for 6 weeks. The results showed that the rats on the HD-M diet had the lowest body weight gain compared to MD-M and LD-M groups (P < 0.05). The total fat dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…Diet and feed were kept constant during the experimental period in other to rule out any source of variation. Animal studies have shown that mushroom enriched diet have no effect on body weight (Handayani et al, 2011). Whitley et al (2009) reported that a commercial probiotic had no effect on body weight of goats as observed in treated animals in our study.…”
Section: Discussioncontrasting
confidence: 42%
“…Diet and feed were kept constant during the experimental period in other to rule out any source of variation. Animal studies have shown that mushroom enriched diet have no effect on body weight (Handayani et al, 2011). Whitley et al (2009) reported that a commercial probiotic had no effect on body weight of goats as observed in treated animals in our study.…”
Section: Discussioncontrasting
confidence: 42%
“…Using a Shiitake mushroom-enriched diet to lower plasma lipid has been widely reported [1,2,3,4]. More recently, the role of Shiitake mushrooms in preventing body weight gain has been reported but its mechanism was largely unknown [5]. The previous study identified that a Shiitake mushroom-enriched diet in rats fed a high fat diet (HFD) significantly lowered plasma triacylglycerol (TAG) and fat deposition by −55% and −35%, respectively, compared to HFD alone [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mushroom is an important natural source of medicine and healthy food with high nutrition, low-calorie, high quality proteins, vitamins and minerals (El Enshasy et al, 2013). Dietary supplementation with Shiitake mushrooms in a high-fat diet can prevent body weight gain, fat deposition, and plasma TAG (triacylglycerol) in rats (Handayani et al, 2011).In general, the ability of medicinal mushrooms as immunestimulator is occurred via innate immunity that typically mediated by phagocytic cells. Phagocytic cells interact with pathogen components or ingest invading them that in either case further serve as stimulator for innate and adaptive immunity through cytokines and chemokine secretion (Hetland et al, 2008).…”
mentioning
confidence: 99%